Jestĕ k optimálnímu slození perorálního steroidního kontraceptiva - Presl, J (Ceskoslovenska gynekologie, 1977)
The effects of exogenous estrogens on the liver are considered to be 1 of the more difficult obstacles in working out an optimal steroid contraceptive, as the liver is 1 of the specific terminal organs for estrogens. The estrogens used in oral steroid contraceptives are ethinyl estradiol (EE) and mestranol (ME). Attempts to overcome the effects of these exogenous estrogens has lead to investigations of the possibilities of gestagens, which have a significant effect on cytoplasmatic receptors in the cells of the terminal tissues. An optimal steroid compound, which maximizes the contraceptive action while minimizing the side effects has been worked out, consisting of daily doses of .03 mg of EE and .15 mg of d-norgestrel. This compound is considered to sufficiently compensate the estrogen effects of its estrogen component through the action of the gestagen component.
Keywords: Female; Levonorgestrel--administraction and dosage; Contraceptives, Oral; ženské pohlaví; Contraceptive Agents, Estrogen--administraction and dosage; Family Planning; lidé; Contraception; kontraceptiva orální hormonální; Ethinyl Estradiol--administraction and dosage; Contraceptive Agents, Female--administraction and dosage; Contraceptive Agents--administraction and dosage; Contraceptives, Oral, Hormonal; Oral Contraceptives--side effects; Mestranol--administraction and dosage; kontraceptiva orální; Contraceptive Agents, Progestin--administraction and dosage; Contraceptive Methods--side effects; Humans